Effect of surface treatments on the localized corrosion resistance of the AA2198‐T8 aluminum lithium alloy welded by FSW process. (11th February 2019) - de S. C. Machado, Caruline; Klumpp, Rafael E.; Ayusso, Victor H.; Donatus, Uyime; Milagre, Mariana X.; de S. Araujo, João V.; F. Machado, Glauson A.; Costa, I.
Abstract : In this work, the effect of eight types of surface treatments on the corrosion resistance of friction stir welded samples of an AA2198‐T8 Al‐Cu‐Li alloy were tested and compared in an attempt to find suitable alternatives to toxic and carcinogenic hexavalent chromium treatments. All the samples were anodized and subjected to different post‐anodizing treatments. The post‐anodizing treatments were (1) hydrothermal treatment in Ce (NO3 )3 6H2 O solution; (2) hydrothermal treatment in Ce (NO3 )3 6H2 O solution with H2 O2 ; (3) hydrothermal treatment in boiling water; (4) hexavalent chromium conversion coating; and (5) immersion in BTSE (bis‐1, 2‐(triethoxysilyl) ethane. The corrosion resistance of the treated samples was evaluated by immersion tests in sodium chloride solution (0.1 mol L −1 NaCl) and electrochemical impedance spectroscopy (EIS) of the friction stir weldment. The results showed that among the alternative treatments, the Ce‐containing solutions presented the best corrosion resistance, especially when used without peroxide.